Framework for Investigating Contractor Selection Decision Support Systems’ (CS-DSS) Acceptance by Public Procurement Personnel - Salla, D. E.; Musa-Haddary, Y. G.; Kolo, B. A.; Gandu, Y. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Laboratory-based designs of contractor selection decision support systems (CS-DSSs) are common in construction management research. However, target end-users like the public procurement entities do not usually make use of these ubiquitous technologies in practice, in spite of their enormous potentials. The absence of reliable framework for investigating technology adoption in public procurement has continued to impede the possibilities of investigating the acceptance of such technologies. The present study aims at developing a framework for investigating CS-DSS acceptance for the smallest decision making unit in public procurement. The structure of a novel theoretical techno-psychological framework for investigating CS-DSS acceptance in Nigerian public procurement is presented in this paper through the lens of an extended innovation diffusion theory - technology acceptance model (IDT-TAM). From an individual level remit (micro-level), a strategic review of literature was followed by a Delphi survey of carefully selected 18-number procurement experts in Nigeria. The study shows that the prescriptions of CS-DSSs by researchers can be supported by a foresight on the end-user behavioral intension to use such technologies. Operationalization of the framework with empirical data can model the acceptance behavior of procurement personnel on CS-DSSs before they are adopted at the organizational or strategic level for enhanced contractor selection in public procurement. The emerging framework is recommended for designers of CS-DSS for articulating the antecedent behavior of public procurement personnel.